THE ART OF OFFICIAL TEXT ANALYSIS: DECODING MEANING, CONTEXT, AND IMPLICATIONS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article presents a comprehensive examination of the linguistic disparities between English and native languages across various dimensions: phonetics, phonology, grammar, semantics, etymology, lexicon, and style. It explores how these differences create challenges and opportunities for language learners, highlighting the uniqueness of English in its phonetic diversity, grammatical structure, semantic complexity, etymological influences, lexical richness, and stylistic versatility. The article emphasizes the contrast between English and native languages, showcasing how these differences shape communication and linguistic understanding.